Financial development and economic growth: Evidence from South Korea between 1961 and 2013 - Samuel Moon Jung (International Journal of Management, Economics and Social Sciences (IJMESS), 2017)
This paper investigated the long run relationship between financial development and economic growth in South Korea using a four-variable Vector Autoregressive (VAR) model using time series data from 1961 to 2013. Applying unit root tests and co-integration analysis, the study revealed that real GDP per capita, financial development, real exports, and real imports were co-integrated with one vector. The empirical results from Granger causality tests based on vector error correction model (VECM) with one co-integrating vector suggested that financial development led to increase in economic growth and that there was unidirectional causality from financial development to economic growth but not from economic growth to financial development, supporting previous theoretical perspectives on the positive relationship between financial development and economic growth. This result emphasized the important role of financial development in South Korea's recent economic growth.
Keywords: L96; O32; 330; Financial Intermediary; Economic Growth; VAR; VECM; Granger Causality